Power transition theory as naval diplomatic practice : an analysis of the United States of America and the people's Republic of China in the Indian ocean from 2017 - 2023 - Blake, Robin (University of Pretoria, 2024)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2023.